Deterministic Elements of Promoting Financial Services - Kurihara, Yutaka (Advances in Social Sciences Research Journal, 2020)
Recently, FinTech (financial technology) and related services have improved greatly. Along with this trend, AI (artificial intelligence) has received a lot of attention as well. Financial institutions have been introducing FinTech and AI for improving efficiency and the quality of services. The aim of this study is to investigate the deterministic elements of promoting financial services. Focusing on two elements, 1) human skills and 2) social circumstances, empirical analyses are conducted to examine the deterministic elements. The empirical results show that finance skill and digital technological skill are both deterministic elements of financial services. Additionally, population growth, finance and banking regulation, and development and application of technology are also deterministic elements. However, whether the population over 65 years is a deterministic elements or not is not clear. To promote the quality of financial services, not only are human skills important, but social circumstances are also important. To make the circumstances clear is inevitable to promote financial services and to improve efficiency. Making these elements a reality, people will be able to enjoy high quality financial services.